Randomised trial of analgesic effects of sucrose, glucose, and pacifiers in term neonates - Carbajal, R (British Medical Journal, 1999)
OBJECTIVES: To assess and compare the analgesic effects of orally administered glucose and sucrose and pacifiers. To determine the synergistic analgesic effect of sucrose and pacifiers. DESIGN: Randomised prospective study with validated behavioural acute pain rating scale. SETTING: Maternity ward. PARTICIPANTS: 150 term newborns undergoing venepuncture randomly assigned to one of six treatment groups: no treatment; placebo (2 ml sterile water); 2 ml 30% glucose; 2 ml 30% sucrose; a pacifier; and 2 ml 30% sucrose followed by a pacifier. RESULTS: Median (interquartile) pain scores during venepuncture were 7 (5-10) for no treatment; 7 (6-10) for placebo (sterile water); 5 (3-7) for 30% glucose; 5 (2-8) for 30% sucrose; 2 (1-4) for pacifier; and 1 (1-2) for 30% sucrose plus pacifier. Mann-Whitney U test P values for comparisons of 30% glucose, 30% sucrose, pacifier, and 30% sucrose plus pacifier versus placebo (sterile water) were 0.005, 0.01, <0.0001, and <0.0001, respectively. Differences between group median pain scores for these comparisons were 2 (95% confidence interval 1 to 4), 2 (0 to 4), 5 (4 to 7), and 6 (5 to 8), respectively. P values for comparisons of 30% glucose, 30% sucrose, and 30% sucrose plus pacifier versus pacifier were 0.0001, 0.001, and 0.06, respectively. Differences between group medians for these comparisons were 3 (2 to 5), 3 (1 to 5), and 1 (0 to 2), respectively. CONCLUSION: The analgesic effects of concentrated sucrose and glucose and pacifiers are clinically apparent in newborns, pacifiers being more effective than sweet solutions. The association of sucrose and pacifier showed a trend towards lower scores compared with pacifiers alone. These simple and safe interventions should be widely used for minor procedures in neonates.